Respostas
respondido por:
3
B){x - 2y = 6
{x + 2y = 2
2x = 8 x - 2y = 6
x = 8/2 4 - 2y = 6
x = 4 -2y = 6 - 4
-2y = 2.(-1)
2y = -2
y = -2/2
y = -1
S={(4,-1)}
C){x + y = 4
{x - y = 11
2x = 15 x + y = 4
x = 15/2 15/2 + y = 4
15/2 + 2y/2 = 8/2
15 + 2y = 8
2y = 8 - 15
2y = -7
y = -7/2
S={(15/2,-7,2)}
{x + 2y = 2
2x = 8 x - 2y = 6
x = 8/2 4 - 2y = 6
x = 4 -2y = 6 - 4
-2y = 2.(-1)
2y = -2
y = -2/2
y = -1
S={(4,-1)}
C){x + y = 4
{x - y = 11
2x = 15 x + y = 4
x = 15/2 15/2 + y = 4
15/2 + 2y/2 = 8/2
15 + 2y = 8
2y = 8 - 15
2y = -7
y = -7/2
S={(15/2,-7,2)}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás